Constructional Design of Bamboo Slanted Ceiling for Lower Material Surface’s Temperature and Humidity Levels - Nabila Afif; Eugenius Pradipto; Maria Ariadne Dewi Wulansari; Riri Chairiyah (RUAS (Review of Urbanism and Architectural Studies), 2019)
In Indonesia, a bamboo slanted ceiling is one of the most commonly used types of ceiling. It occurs for numerous reasons, including technical and cultural aspects. However, practically, it has low durability and is difficult to maintain as it is used in place which is prone to rainwater seepage and installed in the form of large woven sheet material. Therefore, in this research, three alternative models of construction for a bamboo slanted ceiling were proposed: (1) one layer of dense bamboo slats, (2) two layers of dense bamboo slats; and (3) two overlapping layers of sparsely weaved bamboo slats. Each model was developed on a real scale prototype and tested in terms of its material’s temperature and humidity level. The construction strategies used for these models were focused on the arrangement and orientation of pieces of ‘Bambu Kuning’ within the roof structure. The measurement result shows that the third model had the lowest temperature with >5°C different compared to the other models during the hottest hour of the day (from 9 AM to 3 PM). Then, in terms of the humidity measurement, data shows that the second model had the lowest humidity measurement with 1.93% different compared to the first model and 1.22% different compared to the third model. Furthermore, other potential benefits of the proposed models are also presented.